2017
DOI: 10.3332/ecancer.2017.745
|View full text |Cite
|
Sign up to set email alerts
|

Radioguided localisation of non-palpable lesions of the breast in Costa Rica: Review of results of our first 800 patients in private practice

Abstract: BackgroundSurgical treatment of non-palpable breast lesions is controversial. At the European Institute of Oncology in Milan, Italy, Prof Umberto Veronesi introduced a new technique called the radioguided occult lesion localisation (ROLL) in 1996 to replace conventional methods and their disadvantages (Zurrida S, Galimberti V, and Monti S et al (1998) Radioguided localization of occult breast lesions Breast 7 11–13 https://doi.org/10.1016/S0960-9776(98)90044-3). Given the success experienced in that institutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 14 publications
0
1
0
1
Order By: Relevance
“…Initial studies evaluating ROLL suggested its superiority to wire localization and the large experience reported by the European Institute of Oncology in Milan supported its role in breast surgery . However, recently, Aguilar et al analyzed 816 patients with nonpalpable breast lesions undergoing ROLL, but in 42/816 (5.1%) it was not successful because of the following reasons: The radiotracer was not injected sufficiently close to the lesion (n = 22), the radiotracer was administered inside the ducts or in a lymphatic vessel, diffusing in the breast (n = 20), the scintigraphy revealed no radioactivity, and the procedure had to be repeated (n = 2); in particular, because of radiopharmaceutical spreading and subsequent larger excised tissue volume, subcutaneous and intraductal lesions were not “recommended” for ROLL: Our experience regarding mainly ductal/intraductal breast carcinomas permits to state that IUSS technique can be preferred in such cases, overcoming these ROLL limitations and establishing additional indications for IUSS in breast surgery. Namely, since ROLL technique is performed using radiopharmaceutical administration, IUSS approach can be preferred when ROLL is contraindicated or when patients refuse to undergo wire/tag/seed placement.…”
Section: Discussionmentioning
confidence: 99%
“…Initial studies evaluating ROLL suggested its superiority to wire localization and the large experience reported by the European Institute of Oncology in Milan supported its role in breast surgery . However, recently, Aguilar et al analyzed 816 patients with nonpalpable breast lesions undergoing ROLL, but in 42/816 (5.1%) it was not successful because of the following reasons: The radiotracer was not injected sufficiently close to the lesion (n = 22), the radiotracer was administered inside the ducts or in a lymphatic vessel, diffusing in the breast (n = 20), the scintigraphy revealed no radioactivity, and the procedure had to be repeated (n = 2); in particular, because of radiopharmaceutical spreading and subsequent larger excised tissue volume, subcutaneous and intraductal lesions were not “recommended” for ROLL: Our experience regarding mainly ductal/intraductal breast carcinomas permits to state that IUSS technique can be preferred in such cases, overcoming these ROLL limitations and establishing additional indications for IUSS in breast surgery. Namely, since ROLL technique is performed using radiopharmaceutical administration, IUSS approach can be preferred when ROLL is contraindicated or when patients refuse to undergo wire/tag/seed placement.…”
Section: Discussionmentioning
confidence: 99%
“…Los inconvenientes que presenta y que pueden condicionar fallos en la técnica son: lesiones menores de 5 mm, lesiones localizadas en el cuadrante central de la mama, que el radiotrazador pueda difundirse cuando éste se inyecta dentro de los ductos o en los vasos linfáticos, dificultando la exéresis de la lesión. Otros inconvenientes son la contaminación de la piel (0,5%) y del trayecto de la aguja (19%) [20][21] .…”
Section: Discussionunclassified